In silico and biological analysis of anti-androgen activity of the brominated flame retardants ATE, BATE and DPTE in zebrafish. (25th May 2015) - Pradhan, Ajay; Asnake, Solomon; Kharlyngdoh, Joubert Banjop; Modig, Carina; Olsson, Per-Erik
Highlights: In silico analysis with MOE and ICM docking software shows that ATE, BATE and DPTE can bind to zebrafish androgen receptor. ATE, BATE and DPTE are antagonists to zebrafish AR. BATE and DPTE are teratogenic. ATE, BATE and DPTE down-regulate genes involved in steroidogenesis. Abstract: The brominated flame retardants (BFRs) 1, 2-dibromo-4-(1, 2-dibromoethyl)cyclohexane (TBECH or DBE-DCBH) and allyl 2, 4, 6-tribromophenyl ether (ATE or TBP-AE) are alternative BFRs that have been introduced to replace banned BFRs. TBECH is a potential endocrine disrupter in human, chicken and zebrafish and in a recent study we showed that ATE, along with the structurally similar BFR 2, 3-dibromopropyl 2, 4, 6-tribromophenyl ether (DPTE or TBP-DBPE) and its metabolite 2-bromoallyl 2, 4, 6-tribromophenyl ether (BATE or TBP-BAE) are potential endocrine and neuronal disrupters in human. In this study we analyzed ATE, BATE and DPTE for zebrafish androgen receptor (zAR) modulating properties. In silico analysis with two softwares, Molecular Operating Environment (MOE) and Internal Coordinate Mechanics (ICM), showed that ATE, BATE and DPTE bind to zAR. In vitro AR activation assay revealed that these three BFRs down-regulate 11-ketotestosterone (KT) mediated zAR activation. Exposure to 10 μM DPTE resulted in reduced hatching success and like TBECH, BATE and DPTE at 10 μM also had teratogenic properties with 20% and 50% back-bone curvature respectively. Gene transcription analysis in zebrafish embryos as well as in juveniles showed down-regulation of the androgen receptor and androgen response genes, which further support that these BFRs are androgen antagonists and potential endocrine disrupting compounds. Genes involved in steroidogenesis were also down-regulated by these BFRs. In view of this, the impact of these BFRs on humans and wildlife needs further analysis.